Realizing Learners’ Writing Problem from the Beginning: A Case Study - Wahyu Mahendra, Made (ELLITE, 2017)
Abstract The importance of writing has become a primary concern in teaching English as a foreign language. The skill of writing enables learners to generate ideas into certain organisation and awareness once the process of writing is undertaken. From writing, learners are also expected to be able to construct and use the language more accurately because they have enough time to think compared to have an oral activity. However, such an ideal situation can hardly be manifested due to particular problems faced by learners. This present study aims at investigating the struggling points of writing construction done by students. There were fourteen students who were purposefully selected as the subject of this study. In order to gather the supporting data, the researcher employs document study and direct observation. This study is expected to give contribution to help teachers confirming common problems faced by students during learning writing. Nevertheless, it also contributes to other prospective studies which are on the same interest with this present one. Keywords : Assessing Writing, Writing Problems, Writing Construction